Pengaruh Efektivitas Pelayanan Dan Kepuasan Pelanggan Pada Servis Ac (Air Condicioner) Cv Lucky Putra Perkasa Kota Pontianak - Jang, Paulinus (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2024)
This research process was carried out through the process of distributing questionnaires and direct interviews with customers and business owners of CV Lucky Putra Perkasa, Pontianak City. Even though this type of business is widely carried out in Pontianak City, researchers are interested in studying it. The main objectives of this research itself are (1) To determine the effect of service effectiveness on customer satisfaction in CV Lucky Putra Perkasa AC (air conditioner) service, Pontianak City, (2) To determine the effect of obstacles in improving service on customer satisfaction in AC (air conditioner) service. conditioner) CV Lucky Putra Perkasa Pontianak City, (3) To determine efforts to overcome the influence of obstacles in improving AC (air conditioner) service at CV Lucky Putra Perkasa Pontianak Branch. The data collection methods used are questionnaire methods, interview methods and documentation methods. The results of the research based on respondents' answers from the questionnaire show that overall the influence of the effectiveness of the service of AC (air conditioner) service personnel at CV Lucky Putra Perkasa Pontianak Branch is very good, the results of the research show that reliability, responsiveness, guarantee ( assurance), empathy (empathy) and physical evidence (tangible) based on the average of respondents' answers with a high interval rating scale between 61% - 80%.